MIGRATION, MONEY, AND MARGINS: REMITTANCES AND POVERTY DYNAMICS IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
This article estimates the role of remittance inflows in decreasing poverty in Pakistan (measured by per capita income -PCI). for this purpose, an annual time series data is taken from 2010−2025. The method of analysis: The study was based on the quantitative nature using regression and correlation analysis to obtain magnitude of the coefficient (strength) relationship, direction and level of relationship/remittance inflow with respect to income household. The results show the presence of a statistically positive moderate correlation, suggesting that higher remittances inflows lead to higher PCI and reduction in poverty. The regression analysis shows that remittances are significant in reducing the poverty level, accounting for a substantial share of per capita income variation. Household income is a factor that would drive poverty downwards, the study says and this can only become significant if it is accompanied by remittances-enabling and financial inclusion policies, investment in migrants’ (and families’) productive capacity and regional policies where they are hosted. Finally, the results have offer policy implications to the Pakistan policymakers and financial institutions regarding utilization of remittance flow as a source for sustainable development & poverty alleviation.